2006
DOI: 10.1111/j.1399-3046.2005.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

Capsule endoscopy as a diagnostic tool in the evaluation of graft‐vs.‐host disease

Abstract: Capsule endoscopy is a relatively new technology that has allowed gastroenterologists to visualize the mucosa of the small intestine. This technology is playing an expanding role in both adult and pediatric gastroenterology. In this report, we present an 8-yr-old child following allogeneic hematopoietic cell transplantation who developed large volume bloody diarrhea requiring multiple packed red blood cell transfusions that was resistant to aggressive therapy for GVHD. The capsule endoscopy performed on this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 7 publications
0
17
0
1
Order By: Relevance
“…Studies of adult patients have revealed that CE is superior to the small bowel series for evaluating the small intestine [1][2][3]. A number of recent studies on pediatric patients have demonstrated that CE is also a useful in children with abdominal complaints, although the application of CE in this patient population has received relatively less attention compared to the adult patient population [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The indications for CE in both children and adults include obscure gastrointestinal bleeding (OGIB), Crohn's disease (CD), and lymphangiectasia; in adults, suspected tumors of the small bowel also suggest the need for CE [9,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of adult patients have revealed that CE is superior to the small bowel series for evaluating the small intestine [1][2][3]. A number of recent studies on pediatric patients have demonstrated that CE is also a useful in children with abdominal complaints, although the application of CE in this patient population has received relatively less attention compared to the adult patient population [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The indications for CE in both children and adults include obscure gastrointestinal bleeding (OGIB), Crohn's disease (CD), and lymphangiectasia; in adults, suspected tumors of the small bowel also suggest the need for CE [9,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand May et al [77] clearly demonstrated that when chronic abdominal pain is associated with other signs or symptoms (weight loss > 10% of body weight, inflammation shown by laboratory tests, chronic anemia, or suspected mid-gastrointestinal bleeding) relevant, or potentially relevant, findings are diagnosed by capsule endoscopy in about 60% of cases. C a p s u l e e n d o s c o p y h a s a l s o b e e n u s e d , w i t h promising results, in other rare clinical conditions such as indeterminate colitis [78,79] , small bowel transplantation [80] , graft versus host disease [81,82] , protein losing entheropathy [83] , primitive lymphangectasia [84] (mostly in the pediatric population), Whipple disease [85] and irritable bowel syndrome (with clinical suspicion of celiac disease) [86] .…”
Section: Other Indicationsmentioning
confidence: 99%
“…A previous report demonstrated that CE contributed to identify the extent of the small intestinal involvement of HSP and confirmed the efficacy of cyclophosphamide therapy in improving the gastrointestinal lesions (Preud 'Homme DL, 2006). In regard to GVHD, a previous study reported that in an 8-yr old child following allogeneic hematopoietic cell transplantation who developed large volume bloody diarrhea requiring multiple blood transfusions that was resistant to aggressive therapy for GVHD, CE provided significant information not provided by upper endoscopy and colonoscopy that allowed for successful treatment changes (Silbermintz, 2006). Another study (Yakoub-Agha I, 2004) in adults demonstrated that CE provided more significant findings than upper endoscopy in the diagnosis of intestinal GVHD.…”
Section: Othersmentioning
confidence: 98%
“…Thus, Growth failure with additional symptom might be included as an indication for CE. As an optional application, CE can be applied to evaluate the management of gastrointestinal diseases such as Henoch-Schonlein purpura (HSP) (Preud'Homme DL, 2006) and GVHD (Silbermintz, 2006;Yakoub-Agha I, 2004). In HSP, sastrointestinal bleeding occurs in ~50% of children, and massive bleeding may occur (Katz, 1991).…”
Section: Othersmentioning
confidence: 99%